Apparatus for Histological Validation of In Vivo and Ex Vivo Magnetic Resonance Imaging of the Human Prostate - Bourne, Roger M.; Bailey, Colleen; Johnston, Edward William; Pye, Hayley; Heavey, Susan; Whitaker, Hayley; Siow, Bernard; Freeman, Alex; Shaw, Greg L.; Sridhar, Ashwin; Mertzanidou, Thomy; Hawkes, David J.; et al. (Frontiers in Oncology, 2017)
This article describes apparatus to aid histological validation of magnetic resonance imaging studies of the human prostate. The apparatus includes a 3D-printed patient-specific mold that facilitates aligned in vivo and ex vivo imaging, in situ tissue fixation, and tissue sectioning with minimal organ deformation. The mold and a dedicated container include MRI-visible landmarks to enable consistent tissue positioning and minimize image registration complexity. The inclusion of high spatial resolution ex vivo imaging aids in registration of in vivo MRI and histopathology data.